2023
DOI: 10.1017/9781108979801
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic Awareness in Second Language Reading Development

Abstract: This Element aims to address the complexity of metalinguistic awareness to achieve a thorough account of its impacts on second language (L2) reading development and promote an in-depth understanding of the factors regulating the influence of first language (L1) metalinguistic awareness on L2 reading. It is guided by four questions: 1) To what extent do L1 phonological, orthographic, and morphological awareness correlate with L2 phonological, orthographic, and morphological awareness in L2 readers? 2) To what e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 158 publications
1
15
0
Order By: Relevance
“…Developmentally, the importance of MA, and its relative importance with that of PA, is also in line with stage/phase models of reading acquisition where English-speaking children at a relative late stage (e.g., the consolidated alphabetic phase in Ehri, 2005) employ chunking (e.g., syllables and morphemes) to read multisyllabic/multimorphemic words. Numerous studies have found MA as a significant predictor, over and above phonological skills, of both word reading accuracy and fluency across languages and reader groups (see the meta-analytic findings reported in Ke et al, 2021Ke et al, , 2023Lee et al, 2022;Ruan et al, 2018).…”
Section: Morphological Awareness and Reading Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmentally, the importance of MA, and its relative importance with that of PA, is also in line with stage/phase models of reading acquisition where English-speaking children at a relative late stage (e.g., the consolidated alphabetic phase in Ehri, 2005) employ chunking (e.g., syllables and morphemes) to read multisyllabic/multimorphemic words. Numerous studies have found MA as a significant predictor, over and above phonological skills, of both word reading accuracy and fluency across languages and reader groups (see the meta-analytic findings reported in Ke et al, 2021Ke et al, , 2023Lee et al, 2022;Ruan et al, 2018).…”
Section: Morphological Awareness and Reading Developmentmentioning
confidence: 99%
“…Concurrently, none of the recent meta-analyses on correlations of MA with reading outcomes (Ke et al, 2021(Ke et al, , 2023Lee et al, 2022;Ruan et al, 2018) focused on DHH students in specific.…”
Section: Moprhology and Reading In Dhh Students 14mentioning
confidence: 99%
“…But, it is the development of literacy that generates further development of metalinguistic awareness. Ke et al (2023) maintain that learning to read is "fundamentally metalinguistic because learners need to understand how the internal elements of a spoken word relate to units of graphic symbols" (p. 1). They also emphasize reciprocal, developmental relations among oral language, metalinguistic awareness, and reading competence.…”
Section: Mlat Subtest Scores Versus Mlat Composite Score For Predicti...mentioning
confidence: 99%
“…To our knowledge, this is the first systematic review and meta-analysis focused on correlations between sign language and spoken/written language competences, among many other reviews and discussions on related topics over the past few decades (e.g., Cummins, 2007;Grosjean, 2010;Hermans et al 2010;Hoffmeister, 2000;Mayer & Wells, 1996;Mayer & Trezek, 2000;Paul & Yan, 2023;Sanzo, 2022;Scott, 2021;Swanwick, 2016;Wilbur, 2000). There have been a few meta-analyses of cross-linguistic correlations in second language (L2)/bilingual learners (e.g., Branum-Martin et al, 2012;Ke et al, , 2023Melby-Lervåg & Lervåg, 2011;Prevoo et al, 2016;Yang et al, 2017). None, however, focused on signing d/Deaf learners or bimodal bilinguals.…”
Section: Sign Language In D/deaf Students' Spoken/written Language De...mentioning
confidence: 99%
“…This body of the literature, nevertheless, also revealed the complexity of linguistic interdependence and transfer concerning the strength, mechanisms, and directionality of crosslinguistic associations. It also demonstrated that transfer is conditioned on various factors such as Sign Language Transfer 9 L1-L2 distance, L1/L2 proficiency, language complexity, education settings, and research methodology (Chung et al, 2019;Hipfner-Boucher & Chen, 2016) The LIH and transfer facilitation, and their conditioning and complexity, have also motivated efforts to synthesize the findings in a few meta-analyses of cross-linguistic correlation coefficients (Branum-Martin et al, 2012;Ke et al, , 2023Melby-Lervåg & Lervåg, 2011;Prevoo et al, 2016;Yang et al, 2017). These meta-analyses all focused on hearing school-aged students' reading development (e.g., word reading and reading comprehension) with Prevoo et al (2016) being an exception, which examined school outcomes more broadly that also included math and general academic achievement.…”
Section: Linguistic Interdependence Transfer Facilitation and Educati...mentioning
confidence: 99%